Synergy of Investment Law Transformation in the Implementation of PPP for Solar Power Plant Financing in Ibu Kota Nusantara - Gunawan, Muhammad Gilang; Dirkareshza, Rianda (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
The development of Ibu Kota Nusantara (IKN) embraces a sustainable city concept, targeting 100% renewable energy utilization and achieving Net Zero Emission by 2045. Based on Presidential Regulation No. 63 of 2022, IKN's primary energy source comes from Solar Power Plants (PLTS). However, financing this project faces major challenges due to limited capital access and high loan interest rates. The government has established the Public-Private Partnership (PPP) scheme as the main financing mechanism, covering 54% of IKN’s total budget. Nevertheless, the PPP scheme remains highly dependent on high-risk bank loans. Therefore, this study analyzes the optimization of PPP in the PLTS project at IKN by exploring the blended finance scheme, particularly integrating PPP with green bonds. Additionally, it examines the legal aspects of investment in PLTS infrastructure development at IKN and the role of regulations in supporting sustainable financing implementation. This study is expected to provide academic and practical contributions by formulating regulatory recommendations to optimally support energy infrastructure development at IKN. The research employs a normative legal method with a legislative approach, a conceptual approach, and a comparative approach. The findings indicate that issuing green bonds by the IKN Authority can serve as a strategic legal foundation for sustainable PLTS infrastructure financing and attract investors.